An incremental approach to the in-city relocation of informal settlement households along Manila City's esteros - Alampay, Pablo Emilio F.; Santos, Frederick C. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
Due to rapid urbanization, the esteros of Manila have been seeded with Informal-settler families (ISFs) with homes characterized by a lack of basic sanitation systems, unsafe housing locations, and overcrowding. Despite relocation program efforts from multiple government bodies, ISFs return to these hazard zones since off-city relocation disrupts the existing networks of these communities and bar them from urban advantages. Additionally, its top-down approach lacks community input resulting in a mediocre quality of life for the residents. Although on-site upgrading could potentially be a direct solution to the relocation problem, it is unfeasible to execute along the hazard-prone zones of the esteros. In-city migration, given the effects of urbanization, is inevitable, and cities should start to embrace Informal Settlement with standard protocol.
In an attempt to bridge these gaps, a close proximity in-city relocation project was proposed for residents along Estero de La Reina, a rehabilitated area with formerly relocated ISFs returning and rebuilding along this danger zone. Aspects of Incremental upgrading, a strategy that implements iterations through incremental phases, was found to be an effective method to retain the complex network of these communities and their fluctuating needs over time and was used in expansive areas of the architectural design. Consequently, the architectural design solutions follow a bottom-up approach making use of incremental upgrading strategies among small functioning clusters that foster community involvement, networking, and cooperation with the public sector and its stakeholders. This model allows for complete, expandable residential facilities based on direct needs and homeowner input, a retained community network and proximity to income-generating areas, and an opportunity to include adaptive functions good for various future uses. The design ensures the urban poor have adequate space in the city with adaptive capabilities to their fluctuating needs while allowing provision for future migrants to embrace them as a legitimate part of the urban fabric.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Community development, Urban; Relocation (Housing) -- Manila City; Squatter settlements -- Manila City